Maternal contact with social care services and their children’s health and educational outcomes: a data linkage study using mother-baby linkage in ECHILD - Shi, Difei; Jay, Matthew; Harron, Katie (International Journal of Population Data Science, 2025)
Objectives One in four children in England receive children’s social care (CSC) services by age 18. However, it is unclear whether adversity is transmitted intergenerationally when these children become mothers. This study explores the intergenerational effects of maternal experience of CSC on their children's health and educational outcomes. Methods We used the Education and Child Health Insights from Linked Data (ECHILD) database. Maternal social care, education, and health records were linked together and then linked to their children’s education and health records via a mother-baby link. The cohort included 192,380 babies (born 2012–2020) for health outcomes and 7,080 babies (born 2012–2014) for educational outcomes, for mothers born between 1995–2003 and 1995–1997, respectively. Generalised linear models were used to estimate adjusted risk ratios (aRR) for the association between maternal CSC experience and child outcomes, adjusting for maternal characteristics, and with robust standard errors accounting for siblings. Results Babies born to mothers with a history of CSC contact were more likely to be low birthweight (aRR=1.10; 95% CI=1.06-1.14), preterm (aRR=1.06; 95% CI=1.02-1.10), or die before age 1 (aRR=1.24; 95% CI=1.03-1.48), compared to those born to mothers without CSC experience. However, children born to mothers with CSC experience were less likely to have unplanned hospital admissions or Accident and Emergency attendances between ages 1 and 5 than those without, and there were no differences between groups in school readiness at age 5. Some but not all of the associations were explained by other maternal characteristics, including maternal education, age at first delivery, and deprivation. Differences in associations existed between mothers who were Looked After, those with Child Protection Plans, and Children in Need. Conclusion Infants born to mothers with CSC experience are at risk of poor birth and infant outcomes, but these associations do not seem to extend beyond early childhood. Further research is needed to understand how to best support this group of families after children’s social care involvement has finished.